Ichthyofaunal diversity in the community-managed Jagadishpur Reservoir (Ramsar site) and Gajedi Lake, Lumbini Province, Nepal - SANTOSHI SHRESTHA; KUMAR KHATRI; NRIPESH SHRESTHA; RAM CHANDRA POUDEL; KUMAR SAPKOTA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Shrestha S, Khatri K, Shrestha N, Poudel RC, Sapkota K. 2025. Ichthyofaunal diversity in the community-managed Jagadishpur Reservoir (Ramsar site) and Gajedi Lake, Lumbini Province, Nepal. Biodiversitas 26: 3262-3272. This study aimed to establish baseline information on fish species diversity in the Jagadishpur Reservoir and Gajedi Lake, located in Lumbini Province, Nepal, managed under community-based systems. The study was conducted between 2018 and 2022 across three different seasons at five sampling stations using cast nets. Thirty-nine native fish species representing 27 Genera, 18 Families, and 9 Orders were recorded. Among them, Cypriniformes was the dominant order and Danionidae the most widespread family in both water bodies. In Jagadishpur Reservoir, Rasbora daniconius was the most abundant species, followed by Puntius sophore, whereas Amblypharyngodon mola and Trichogaster fasciata were the most common in Gajedi Lake. The Shannon-Wiener diversity index (H') ranged from 1.54 to 2.77, indicating moderate biodiversity. Pielou’s evenness index (J), ranging from 0.72 to 0.93, suggested a relatively even species distribution. Notably, Badis badis and Macrognathus lineatomaculatus were observed only once in the Jagadishpur Reservoir and Gajedi Lake, respectively. Both water bodies were found to be slightly alkaline. The Redundancy Analysis (RDA) results revealed low adjusted R² values for the two lentic systems, suggesting that while environmental variables do influence fish community structure, a substantial portion of the variation remains unexplained, likely due to the complex biotic interactions and unmeasured factors. The findings show that both wetlands support a rich diversity of native fish species and that they contribute to the understanding of fish richness and associated water quality parameters, and provide valuable insights for planning sustainable fishing practices, guiding future research, and informing conservation strategies.